Chemical Composition and Biological Activity of Milk Thistle Seeds (Silybum marianum (L.) Gaertn.) - Doğan, Gülden; Kara, Nazan; Gür, Seher; Bagcı, Eyup (Uğur ÇAKILCIOĞLU, 2022)
Milk Thistle Seeds (MTS) purifies the liver from all toxic and harmful substances, supports the regeneration of liver cells. In this study, the chemical composition of milk thistle seeds (Silybum marianum (L.) Gaertner = Carduus marianus L.) and also its biological activity were determined. Essential oil was analyzed using by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) techniques. After that, the essential oil was tested against bacteria and fungi by agar well diffusion and micro dilution methods. The essential oil yield was 1.1% (v/w). Eight constituents were comprised the 97.3% of the total oil extract of the Milk thistle seeds. The major compounds were determined as oleic acid (45.6%), linoleic acid (29.0%), ethylbenzene (7.0%) and stearic acid (5.7%). The seed essential oils of MTS significantly inhibited the growth of Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Streptococcus sp.) bacteria (p < 0.05). The oils also showed fungicidal activity against Candida tropicalis and C. globrata.
Keywords: Structural Biology; Yapısal Biyoloji